Gender Differential Expression of AR/miR-21 Signaling Axis and Its Protective Effect on Renal Ischemia-Reperfusion Injury - Huang, Gaomin; Yao, Qiu; Ye, Zhenfeng; Huang, Yawei; Zhang, Chiyu; Jiang, Yi; Xi, Xiaoqing (Frontiers in Cell and Developmental Biology, 2022)
Objective The aim of this study was to investigate gender differences after renal ischemia-reperfusion injury in mice and the effects of androgen receptor (AR) and microRNA-21 (miR-21) on apoptosis in renal ischemia-reperfusion injury. Methods Renal ischemia-reperfusion injury model was induced by 45 min of bilateral renal artery ischemia and reperfusion. BALB/c mice were randomly divided into groups according to different experimental protocols. The levels of renal function were evaluated by serum creatinine and blood urea nitrogen. TUNEL staining was used to analyze the pathological changes and apoptosis levels of renal tissue, and western blotting and qPCR were used to detect the expressions of miR-21, AR, PDCD4 and caspase3. Results After renal ischemia-reperfusion injury in mice with different genders, the levels of plasma urea nitrogen and creatinine in female and male mice increased, the histopathological score increased, and TUNEL staining in renal tissue indicated increased apoptosis. The expressions of miR-21, PDCD4, and active caspase-3 protein were up-regulated. The above trend was more pronounced in male mice, and a significant decrease in AR mRNA expression was detected. Silencing the expression of AR aggravated the decline of renal function and renal tubular injury after renal ischemia in mice, and the expression of PDCD4 and active caspase-3 increased, and the level of miR-21 was correspondingly decreased. Up-regulation of miR-21 expression by pre-miR-21 can alleviate renal ischemia-reperfusion injury, negatively regulate PDCD4, reduce the expression level of caspase3, and yet induce AR expression accordingly, thereby inhibiting renal tubular epithelial cell apoptosis. The effect of antagomiR-21 was the opposite, which aggravated renal ischemia-reperfusion injury. Conclusion There are gender differences in renal ischemia-reperfusion injury. Male mice are more susceptible to renal ischemia-reperfusion injury than female, and AR expression is decreased. Silencing AR expression aggravated ischemia-reperfusion injury, promoted the expression of PDCD4 and apoptosis protein caspase3, and decreased the expression level of miR-21. Application of pre-miR-21 to up-regulate endogenous miR-21 can inhibit the expression of PDCD4 and apoptotic protein caspase 3 to exert anti-apoptotic effect, while antagomiR-21 take opposite effect. The protective effect of AR and miR-21 in renal ischemia-reperfusion injury has a certain synergy.